2011
DOI: 10.4103/0970-4388.85831
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgical dentofacial deformities and dental treatment needs in cleft-lip-palate children: A clinical study

Abstract: The study revealed that the distribution of cleft deformity is shown out of 23 male children, 11 children with unilateral cleft lip, 9 children with bilateral cleft lip palate, and remaining 3 children were with cleft palate. Out of 27 female children, 19 children with unilateral cleft lip palate, 3 children with bilateral cleft lip palate, and 5 children with cleft palate. This study showed a wide range of surgical, dental, and functional problems in all operated cleft lip and palate patients. Hence, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…3,4 These erroneous views of cleft etiology may deter the parents from pursuing treatment for fear of disrupting God's plan. [11][12][13][14] What Is This Box? 3 Clefts of the lip and/or palate may occur sporadically or in conjunction with other anomalies as a sequence, such as Pierre Robin, or as part of a syndrome.…”
mentioning
confidence: 99%
“…3,4 These erroneous views of cleft etiology may deter the parents from pursuing treatment for fear of disrupting God's plan. [11][12][13][14] What Is This Box? 3 Clefts of the lip and/or palate may occur sporadically or in conjunction with other anomalies as a sequence, such as Pierre Robin, or as part of a syndrome.…”
mentioning
confidence: 99%
“…In patients with CLP, agenesis of the maxillary lateral incisor, a supernumerary tooth and rotated or displaced teeth are frequency seen dental anomalies (Priya, Reddy, Ramakrishna, & Reddy, 2011). Consequently, most children with CL/P need additional dental and orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pradel et al 11 demonstrates that one-stage repair, at the age between 9 and 12 months, has a positive influence on the initial maxillary growth, in contrast with the two-stage procedure. Despite the description of ideal age for performing palatoplasty in the protocols, a study demonstrated that the time when palatoplasty was performed did not present significant effect on global development of dentofacial skeletal structures 17 .…”
Section: Maxillary Growth and Palatoplastymentioning
confidence: 99%
“…palatoplasty, and present alterations in some aspects, such as resonance and articulation. In the study written by Prya et al 17 , 92% of the subjects, aged 1 to 14, who underwent palatoplasty (with various techniques) presented alteration in speech (without these alterations being specified) 17 . The most common complications of the palate repair procedure are velopharyngeal insufficiency and oronasal fistulae (which may be either asymptomatic or insufficiency causer) 9 .…”
Section: Speech and Palatoplastymentioning
confidence: 99%
See 1 more Smart Citation